Synthesising Artificial Intelligence and Physical Performance. (7th April 2022) - Menges, Achim; Wortmann, Thomas
Abstract: At the Institute for Computational Design and Construction (ICD) at the University of Stuttgart, its founding director Achim Menges, who also directs the Cluster for Excellence for Integrative Computational Design and Construction for Architecture (IntCDC), and tenure‐track professor Thomas Wortmann illustrate some of their group's research into the exploration of material performance and structures utilising AI and robotics.